2012
DOI: 10.1134/s1560090412040070
|View full text |Cite
|
Sign up to set email alerts
|

Controlled radical (co)polymerization of (meth)acrylic esters via the reversible addition-fragmentation chain-transfer mechanism

Abstract: The homopolymerization of acrylic and fluoroacrylic esters mediated by benzyl dithiobenzoate and dibenzyl trithiocarbonate proceeds in the controlled mode via the reversible addition fragmentation chain transfer mechanism, while the controlled radical polymerization of methacrylic esters is not effected under these conditions. The molecular mass characteristics of the copolymers of acrylic and methacrylic esters may be satisfactorily controlled by benzyl dithiobenzoate-mediated copolymerization when the con te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…57,58 The availability of retained trithiocarbonate groups for further reaction was shown by graing of glycerol monomethacrylate with apparent success indicated by morphological changes in the monolith and altered separation of analytes post-graing. However, DBTC is known to be a poor RAFT agent for methacrylates, 29,31,59,60 which casts some doubt on the validity of mechanistic conclusions. Moreover, no characterization by spectroscopic or elemental analysis for detection of the trithiocarbonate groups was provided.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 The availability of retained trithiocarbonate groups for further reaction was shown by graing of glycerol monomethacrylate with apparent success indicated by morphological changes in the monolith and altered separation of analytes post-graing. However, DBTC is known to be a poor RAFT agent for methacrylates, 29,31,59,60 which casts some doubt on the validity of mechanistic conclusions. Moreover, no characterization by spectroscopic or elemental analysis for detection of the trithiocarbonate groups was provided.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments, BTB, which is an efficient RAFT agent in the homopolymerization of acrylates [17,18], was used; thus, there is good reason to believe that the polymerization of isobornyl acrylate in the presence of BTB will proceed via controlled/living mechanism. Figure 1 shows that the molecular weight distribution curves of PIBA samples obtained in the presence of 10 -2 -(5 × 10 -2 ) mol/L BTB shift to the high molecular weight region with monomer conversion.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the RDRP of α-fluorinated acrylates has only been scarcely reported. [39][40][41][42][43][44][45] Boutevin's group 39,40 reported the ATRP of n-butyl -fluoroacrylate (FABu) using ethyl 2-bromoisobutyrate (EBiB) and CuX (X= Br or Cl)/ 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA) as the catalyst. The dispersity of the resulting polymer was as low as 1.14.…”
Section: Introductionmentioning
confidence: 99%
“…40 However, the measured molar masses were quite different from the theoretical values due to the inefficient chain transfer reaction of the CTA employed. To the best of our knowledge, the RDRP of α-fluorinated monomers bearing fluorinated pendent group (1,1,1,3,3,3-hexafluoroisopropyl αfluoroacrylate, FAHFiP) was only reported by Semchikov et al [42][43][44][45] using dibenzyl trithiocarbonate as chain transfer agent (CTA). After determining the reactivity ratios of FAHFiP and N-vinylpyrrolidone (NVP), these authors reported that an alternating copolymer was formed.…”
Section: Introductionmentioning
confidence: 99%